2022
DOI: 10.3991/ijep.v12i2.29333
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effects of University Field Courses on Distance Education

Abstract: This research focuses on examining the effects of university field courses on distance education and the integration of distance education into courses. A group of 357 university students studying biomedical engineering at universities in the Kosovo region and the Russian Federation volunteered to participate in the research.  A quantitative research method was used in the study. In the research, the "Distance Education" measurement tool developed by the researchers was used as a data collection tool. The ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…This finding aligns with the results of this study, demonstrating that the usability of IARE-W influences students' attitudes toward its adoption. Moreover, a comparative analysis with previous studies emphasizes the crucial role of PU in AR technology in influencing students' attitudes [11], [32], [33]. Prior research conducted in various educational settings has demonstrated that the tangible benefits provided by AR technology can impact students' attitudes and acceptance of the technology [8], [18].…”
Section: Discussionmentioning
confidence: 90%
“…This finding aligns with the results of this study, demonstrating that the usability of IARE-W influences students' attitudes toward its adoption. Moreover, a comparative analysis with previous studies emphasizes the crucial role of PU in AR technology in influencing students' attitudes [11], [32], [33]. Prior research conducted in various educational settings has demonstrated that the tangible benefits provided by AR technology can impact students' attitudes and acceptance of the technology [8], [18].…”
Section: Discussionmentioning
confidence: 90%
“…Digitisation is the most advanced. One of the elements in the communication industry is to protect learning for students [21] [10]. The digitalisation of the era that is currently developing rapidly, dramatically affects human life performance [10].…”
Section: Introductionmentioning
confidence: 99%